Optimizing laying hen diets: effect of partial maize meal replacement with wheat bran or biscuits crumbs and Bacillus amyloliquefaciens CECT 5940 - Manteiga, Albertina Felizardo; Changule, Abilio Paulo; Magaia, Dercia Hilario; Manjate, Nilza Jorge; Chilala, Florentina Domingos; Joaquim, Leonel António; Chivale, Eunice Justino; Anjos, Filomena Dos; Tomo, Otilia Henrique Tamele; Garcia-Herreros, Manuel; Bila, Custodio (Frontiers in Veterinary Science, 2025)
BackgroundWheat bran (WB) and biscuit crumbs (BC) offer alternative feed sources for laying hens, potentially improving productivity and economic efficiency.ObjectiveThis work evaluated the partial replacement of maize meal with WB or BC, with or without the addition of Bacillus amyloliquefaciens CECT 5940, on the productive and economic performance of laying hens.MethodsFive treatments were allocated as follows: T1: a basal diet; T2: a basal diet where 20% of maize meal was replaced by WB; T3: a basal diet that included 20% of WB plus B. amyloliquefaciens CECT 5940; T4: a basal diet where 20% of maize meal was replaced by BC; and T5: a basal diet that included 20% of BC plus B. amyloliquefaciens CECT 5940. Productive parameters (live weight, laying rate, feed conversion per egg mass, feed conversion per dozen eggs, feed consumption, and viability) and economic metrics (feed costs, production cost per egg, production cost per dozen eggs, gross revenue, gross added value, profitability index, contribution margins, and break-even point) were assessed using ANOVA and the Tukey test.Main findingsA statistically significant (p < 0.05) increase was observed in the LR and FC/dz when maize meal was partially replaced with BC. While the addition of B. amyloliquefaciens CECT 5940 to WB significantly improved LR and FC/dz when compared to T2 (p < 0.05), no significant difference was seen for BC (p > 0.05). As for the economic evaluation, both T2 and T3 significantly reduced production costs (p < 0.05). Compared to T1, the partial replacement of maize meal with WB significantly reduced (p < 0.05) gross revenue. The addition of B. amyloliquefaciens CECT 5940 significantly increased (p < 0.05) gross value added, profitability index, and contribution margins, and significantly reduced the break-even point (p < 0.05) in comparison with T1 for WB and BC both with (T3 and T5) and without B. amyloliquefaciens CECT 5940 (T2 and T4).ConclusionIt was concluded that the addition of B. amyloliquefaciens CECT 5940 to both WB and BC diets was as efficient as the basal diet in terms of productivity and improved economic performance.